Red Blood Cell Morphodynamics: A New Potential Marker in High-Risk Patients - Porro, Benedetta; Conte, Edoardo; Zaninoni, Anna; Bianchi, Paola; Veglia, Fabrizio; Barbieri, Simone; Fiorelli, Susanna; Eligini, Sonia; Di Minno, Alessandro; Mushtaq, Saima; Tremoli, Elena; Cavalca, Viviana; et al. (Frontiers in Physiology, 2021)
In the last years, a substantial contribution of red blood cells (RBCs) in cardiovascular homeostasis has been evidenced, as these cells are able to regulate cardiovascular function by the export of adenosine triphosphate and nitric oxide as well as to maintain redox balance through a well-developed antioxidant system. Recently a link between high-risk plaque (HRP) features and myocardial ischemia, in the absence of severe lumen stenosis, has been evidenced. Nonobstructive coronary artery disease (nonob CAD) has been associated in fact with a greater 1-year risk of myocardial infarction and all-cause mortality compared with no apparent CAD. This new evidence increases interest in searching new triggers to identify these high-risk patients, in the absence/or on top of traditional hazard markers. In this study we investigated the existence of any association between RBC morphodynamics and HRP features in individuals with different grades of coronary stenosis detected by coronary computed tomography angiography (CCTA). Ninety-one consecutive individuals who underwent CCTA [33 no CAD; 26 non obstructive (nonob) and 32 obstructive (ob) CAD] were enrolled. RBC morphodynamic features, i.e. RBC aggregability and deformability, were analyzed by means of Laser Assisted Optical Rotation Cell Analyzer (LoRRca MaxSis). The putative global RBC morphodynamic (RMD) score and the related risk chart, associating the extent of HRP (e.g. the non-calcified plaque volume) with both the RMD score and the max % stenosis were computed. In nonob CAD group only positive correlations between RBC rigidity, osmotic fragility or aggregability and HRP features (plaque necrotic core, fibro-fatty and fibro-fatty plus necrotic core plaque volumes) were highlighted. Interestingly, in this patient cohort three of these RBC morphodynamic features result to be independent predictors of the presence of non-calcified plaque volume in this patients group. The risk chart created shows that only in nonob CAD plaque vulnerability increases according to the score quartile. Findings of this work, by evidencing the association between erythrocyte morphodynamic characteristics assessed by LoRRca and plaque instability in a high-risk cohort of nonob CAD, suggest the use of these blood cell features in the identification of high-risk patients, in the absence of severe coronary stenosis.